Successful weight loss reduces endothelial activation in individuals with severe obesity participating in a multimodal weight loss program. Issue 3 (May 2021) - Sag, Sabine J.M.; Strack, Christina; Zeller, Judith; Mohr, Margareta; Loew, Thomas; Lahmann, Claas; Maier, Lars S.; Fischer, Marcus; Baessler, Andrea
Highlights: Obesity is associated with changes in vascular structure and endothelial function. Longterm successful weight loss improves vascular function in people with obesity. Successful weight loss may reverse endothelial activation in obesity. Abstract: Introduction: Endothelial dysfunction is a very common finding in obesity and metabolic syndrome. The aim of our study was to investigate if longterm weight reduction (WR) success may reverse endothelial activation in individuals with severe obesity participating in a multimodal WR program. Methods: Participants with obesity (øBMI 40.3 ±7.5 kg/m 2 ) underwent a standardized non-surgical 1-year WR program. Carotid artery studies and determination of endothelial function biomarkers were performed at baseline and after 1 year. Individuals were dichotomized in "successful WR" (% WR≥10% of initial body weight) and "failed WR" (% WR<10% of initial body weight). Results: From 191 people with obesity, 115 achieved successful WR. Compared to controls without obesity (n=44) participants with obesity had higher carotid intima media thickness as well as higher sICAM-1, sE-selectin, MMP-9, hsCRP and IL-6 levels. After 12 months follow up delta values of inflammation and endothelial adhesion markers were significantly different between participants with obesity and successful WR and participants with obesity and failed WR, in favour of the successful WR group (mean ± standard deviation): ΔhsCRP (−5.2 mg/L ±7.8 vs. 1.1 mg/L ±5.1, P<0.001; Padj =0.009), ΔIL-6 (−1.0 pg/mL ±3.4 vs. 0.5 pg/mL ±2.6, P<0.001; Padj =0.057), ΔsE-selectin (−19.0 ng/mL ±24.4 vs. 39.2 ng/mL ±20.3, P<0.001; Padj <0.001), ΔsICAM-1 (-26.4 ng/mL ±68.8 vs. 10.6 ng/mL ±73.9, P=0.004; Padj =0.805) and ΔoxLDL (−4 mg/dL ±30 vs. 5 mg/dL ±25, P=0.004; Padj =0.473). In linear regression analysis reduction of BMI was significantly associated with improvement of several endothelial dysfunction biomarkers with the strongest effects for ΔsE-selectin and ΔhsCRP. Conclusion: Our data corroborate the finding that obesity leads to endothelial dysfunction. Furthermore, successful non-surgical WR may at least partially reverse endothelial activation implicating cardiovascular health benefits of WR in people with severe obesity.